PENGARUH RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM - Euis Ajizah; Bruna Baladika Suheli (Universitas La Tansa Mashiro, 2019)
This research was to determine the factors that effect stock prices through ratios Return On Assets (ROA) and Return On Equity (ROE) in the food and beverage company listed on the Indonesia Stock Exchange 2013 – 2018. The purpose of this study were to determine the effect Return On Assets (ROA) and Return On Equity (ROE) on stock price of shares in the food and beverage company listed on Indonesia Stoc Exchange the period 2013 – 2018.The method used in this research is descriptive quantitative research methods. The sampling technique used was purposive sampling, the method of determination of the respondents to be sampled based on the criteria. The sample in this study consisted of 7 food and beverage companies listed in Indonesia Stock Exchange with a closing stock price highs in 2018. The data was collected by downloading financial data website www.idx.co.id and www.sahamok.com.Testing of thid research was conducted using classic asumnption test, then analyzed with correlation and multiple regression analysis using IBM SPSS program (Statistic Program for Social Science) V.20.The results showed a partial effect between the Return On Assets (ROA) on stock price, t test result on ROA obtained sig 0,036 < 0,005. The result also showed that there was a not effect partially between the Return On Equity (ROE) on stock price, the t test result in ROE obtained sig 0,879 > 0,005.Test result showed 0,000 significance. Because the value of significance 0,000 < 0,005, so it concluded there is significant influence simultaneously between the Return On Assets (ROA) and Return On Equity (ROE) to the price of shares in the food and beverage company listed on the Indonesia Stock Exchange 2013 – 2018.Penelitian ini untuk mengetahui faktor yang mempengaruhi harga saham melalui rasio Return On Assets (ROA) dan Return On Equity (ROE) pada perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia tahun 2013 – 2018. Adapun tujuan dari penelitian ini adalah untuk mengetahui Return On Assets (ROA) dan Return On Equity (ROE) terhadap harga saham pada perusahaan makanan dan minuman yang terdaftar di BEI periode 2013 – 2018.Metode yang digunakan dalam penelitian ini adalah metode penelitian Deskriptif Kuantitatif. Teknik pengambilan sampel yang digunakan adalah purposive sampling, yaitu metode penetapan responden untuk dijadikan sampel berdasarkan kriteria. Sampel dalam penelitian ini terdiri dari 7 perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia dengan harga saham penutupan pada tahun 2013 – 2018. Pengumpulan data dilakukan dengan pengunduhan data laporan keuangan melalui website www.idx.co.id dan www.sahamok.com.Pengujian terhadap penelitian ini dilakukan dengan menggunakan uji asumsi klasik, kemudian dianalisis dengan uji korelasi dan uji regresi linier berganda menggunakan program IBM SPSS (Statistic Program for Social Science) v.20.